P255 Rate of lung function decline in patients with cystic fibrosis (cf) having a residual function gene mutation. (15th November 2017) - Sawicki, G; Konstan, MW; McKone, E; Moss, RB; Lubarsky, B; Suthoff, E; Millar, S; Pasta, DJ; Mayer-Hamblett, N; Goss, CH; Morgan, W
Abstract : Objective: Patients with cystic fibrosis (CF) and mutations associated with residual CFTR chloride transport have improved survival rates compared with those homozygous for the F508del-CFTR mutation. Since little is known about rate of lung function decline in patients with CF and residual function (RF) mutations, we evaluated differences in rates of percent predicted FEV1 (ppFEV1 ) decline between patients with an RF mutation who were heterozygous for F508del and those who were homozygous for F508del, and whether rates of ppFEV1 decline differed across age groups. Methods: Patients in the US CF Foundation Patient Registry from 2006 to 2014 with an RF mutation heterozygous for F508del were compared with F508del -homozygous patients. Mutations were identified based on clinical or in vitro evidence of residual ion transport. Annual rates of ppFEV1 decline were estimated for patients 6 to 45 years of age with ≥3 ppFEV1 values spanning ≥0.5 years in a randomly chosen 2 year period that began at the first ppFEV1 measurement in the calendar year. Results: A total of 1242 RF and 11, 916 F508del- homozygous patients were included. At the first visit, the RF cohort was older (mean [SD], 23.0 [12.1] vs 18.0 [9.6] years) and had better nutritional status (mean [SD] BMI z score, 0.36 [1.09] vs −0.29 [1.08]). Mean (SD) ppFEV1 differed at the first visit between cohorts (80.4 [24.8] vs 73.4 [26.5]; p<0.001). Annual rate of ppFEV1 decline was estimated at −0.70 (SE, 0.20) in the RF cohort compared with −1.91 (0.05) in the F508del -homozygous cohort (p<0.001). After excluding patients with R117H (n=889), the rate of decline was −1.05 (0.39) ppFEV1 per year (p<0.001 vs F508del ). The rate of decline for RF patients was most rapid in the 18 to 24–year age group, −1.38 (0.39), but was still significantly less than the −2.52 (0.09) for F508del -homozygous young adults (p=0.004). Conclusion: Patients with CF and an RF mutation have lower rates of lung function decline compared with F508del -homozygous patients. However, patients with an RF mutation still demonstrate progressive lung disease, particularly during young adulthood. Please refer to page A259 for declarations of interest in relation to abstract P255.